Anatomy of equine incisors: Pulp horns and subocclusal dentine thickness. (7th May 2018) - Englisch, L. M.; Rott, P.; Lüpke, M.; Seifert, H.; Staszyk, C.
Summary: Background: Equine incisors are often reduced in height during corrective dental procedures. Increased knowledge of subocclusal dentine thickness and pulp morphology may help prevent iatrogenic pulpar exposure. Although such data exist for equine cheek teeth, there are currently no reliable data for incisors. Objectives: To measure the distances between pulp cavities and the occlusal as well as the labial surfaces of equine incisors and to test if these distances change with age. Furthermore, pulp morphology with regard to number and orientation of pulp horns was investigated. Study design: Observational study using cadaver material and high‐resolution computed tomography. Methods: Upper and lower incisor arcades were removed from heads of 13 horses and scanned with high‐resolution computed tomography. 3D Models were reconstructed and configuration as well as number of the pulp horns was evaluated. Anatomical marker points were set to measure distances between the pulp horn tips and the labial and occlusal surfaces. Results: Subocclusal dentine thickness ranged between 1.5 and 11.7 mm in upper and 0.7 and 6.7 mm in lower incisors. It decreased with tooth age. Distance to labial aspect ranged between 3.5 and 9.0 mm in upper and 3.8 and 8.1 mm in lower incisors and increased with tooth age. Main limitations: Details of horse management, feeding and previous dental care were not available. Therefore, it remains unknown how these factors influenced the results. Conclusions: Although mean subocclusal dentine thickness of greater than 4.1 mm was found, equine incisors occasionally have less than 1 mm of thickness with potential for iatrogenic pulpar exposure during incisor reduction. Therefore, great care should be exercised by any practitioner during incisor reduction.